Cortical thickness and subcortical structure volume abnormalities in patients with major depression with and without anxious symptoms. Issue 8 (27th June 2017) - Zhao, Ke; Liu, Haiyan; Yan, Rui; Hua, Lingling; Chen, Yu; Shi, Jiabo; Lu, Qing; Yao, Zhijian
Abstract: Background: Anxious depression is one of the common subtypes of major depressive disorder (MDD). Clinically, patients with anxious depression exhibit more severe depressive symptoms than patients with nonanxious depression. The aim of the present study was to explore the common and differing cortical and subcortical structural changes between patients with anxious and nonanxious depression. Methods: Patients were placed into one of three groups: the anxious depression group (MDD patients with high levels of anxiety symptoms, n  = 23), the nonanxious depression group ( n  = 22), and healthy controls ( n  = 43) that were matched for age, sex, and education level. All participants underwent T1‐weighted MRI. The Freesurfer, which uses a set of automated sequences to analyze the abnormal changes of cortical thickness, cortical and subcortical structures, was used to process the T1 images. Results: Compared to controls, MDD patients showed thinner cortical thickness in the left inferior temporal, the right superior temporal, and the right parsorbitalis, and a smaller volume of the left hippocampus. Compared to nonanxious depression, anxious depressive patients showed a cortical thinning of the left superior frontal and right superior temporal, as well as the right lingual, and significantly increased subcortical volume of the bilateral caudate nuclei. Correlation analysis showed that the volumes of the bilateral caudate nuclei were directly proportional to the anxiety/somatization factor score. Conclusions: These findings suggest that smaller hippocampal volume and atrophic prefrontal and temporal cortices might be a common pattern of cortical and subcortical alterations in patients with depression and/or anxiety. However, the change in the caudate nucleus volume may be indicative of anxious depression and may potentially be used to distinguish anxious from nonanxious depression. Abstract : We recruited 23 anxious depression, 22 nonanxious depression and 43 healthy controls, and compared the difference of cortical thickness, cortical and subcortical volume between them. The results showed that smaller volume of hippocampal and atrophic prefrontal and temporal cortex might be a common gray‐matter alteration in depressed patients with or without anxiety. However, the increased volume of caudate nucleus may be the characteristic change of anxious depression.